Growth hormone treatment for growth hormone deficiency and idiopathic short stature: new guidelines shaped by the presence and absence of evidence. Issue 4 (August 2017) - Grimberg, Adda; Allen, David B.
Abstract : Purpose of review: The Pediatric Endocrine Society recently published new guidelines for the use of human growth hormone (hGH) and human insulin-like growth factor-I (hIGF-I) treatment for growth hormone deficiency, idiopathic short stature, and primary IGF-I deficiency in children and adolescents. This review places the new guidelines in historical contexts of the life cycle of hGH and the evolution of US health care, and highlights their future implications. Recent findings: The new hGH guidelines, the first to be created by the Grading of Recommendations Assessment, Development and Evaluation approach, are more conservative than their predecessors. They follow an extended period of hGH therapeutic expansion at a time when US health care is pivoting toward value-based practice. There are strong supporting evidence and general agreement regarding the restoration of hormonal normalcy in children with severe deficiency of growth hormone or hIGF-I. More complex are issues related to hGH treatment to increase growth rates and heights of otherwise healthy short children with either idiopathic short stature or 'partial' isolated idiopathic growth hormone deficiency. Summary: The guidelines-developing process revealed fundamental questions about hGH treatment that still need evidence-based answers. Unless and until such research is performed, a more restrained hGH-prescribing approach is appropriate.